TANTANGAN MASYARAKAT ADAT DALAM MENGHADAPI DINAMIKA HUKUM ADAT DI ERA DIGITAL - Muthiatus Sholikhah; Nabella Serly Margareta; Nadhiva Aliya Az Zahra; Rabmuid Efendi Mulyo (Pojok Publisher, 2025)
Digitalization has brought significant changes to the lives of indigenous communities, particularly in terms of social, economic, and cultural interactions. While it offers conveniences such as faster access to information, digitalization also has the potential to undermine local cultural identity and traditional values. The increasing dependency on technology, which is not equally distributed across indigenous communities, along with the spread of global culture that conflicts with local values, exacerbates this situation. Digitalization can serve as an opportunity to document and disseminate customary law through digital platforms such as social media, cloud-based applications, and GIS. However, the main challenges faced are the digital divide, the potential simplification of essential cultural values, and data security issues. Therefore, strengthening technological infrastructure, digital literacy education, robust data protection, and collaboration among the government, indigenous communities, academics, and technology practitioners are required. Through a holistic and collaborative approach, digitalization can become an effective tool to strengthen the presence of customary law as an integral part of Indonesia’s cultural identity in the modern era.